Interrelationship of Nutrition and Immunity - Gary D. Butcher; Richard D. Miles (EDIS)
The immune system benefits greatly from proper nutrition of the bird. Not only does the immune system benefit directly from proper nutrition, but indirectly proper nutrition will also prepare the bird for periods of stress, reducing the adverse effects of stress and enhancing recovery from stressful periods. Therefore, in many instances, proper nutrition lessens the immune suppression associated with the stress response in the bird. This document is VM139, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 12, 2002.